Reassessing security in the South Caucasus : regional conflicts and transformation / edited by Annie Jafalian - Jafalian, Annie (Routledge Ashgate, 2011)
Lying on the periphery of Europe, Russia, Turkey and Iran, the South Caucasus is receiving growing attention among decision-makers and scholars of international relations. It acts as a corridor for oil and gas imports whose stability has become part of European security itself. This volume reassesses security in the South Caucasus.